Natural variation of arsenic fractions in soils of the Brazilian Amazon - da Silva Júnior, Ediu Carlos; Martins, Gabriel Caixeta; de Oliveira Wadt, Lúcia Helena; da Silva, Kátia Emídio; de Lima, Roberval Monteiro Bezerra; Batista, Karine Dias; Guedes, Marcelino Carneiro; de Oliveira Junior, Raimundo Cosme; Reis, André Rodrigues [UNESP]; Lopes, Guilherme; de Menezes, Michele Duarte; Broadley, Martin R.; et al. (Elsevier, 2019)
Arsenic (As) in native soils of the Amazon rainforest is a concern due to its likely origin from the Andean rivers, which transport loads of sediments containing substantial amounts of trace elements coming from the cordilleras. Yet, unveiling soil As baseline concentrations in the Amazon basin is still a need because most studies in Brazil have been performed in areas with predominantly high concentrations and cannot express a real baseline value for the region. In this study, 414 soil samples (0–20, 20–40 and 40–60 cm layers) were collected from different sites throughout the Amazon basin - including native Amazon rainforest and minimally disturbed areas - and used to determine total and extractable (soluble + available) As concentrations along with relevant soil physicochemical properties. Descriptive statistics of the data was performed and Pearson correlation supported by a Principal Component Analysis (PCA) provided an improved understanding of where and how As concentrations are influenced by soil attributes. Total As concentration ranged from 0.98 to 41.71 mg kg−1 with values usually increasing from the topsoil (0–20 cm) to the deepest layer (40–60 cm) in all sites studied. Considering the proportional contribution given by each fraction (soluble and available) on extractable As concentration, it is noticeable that KH2PO4-extractable As represents the most important fraction, with >70% of the As extracted on average in all the sites studied. Still, the extractable fractions (soluble + available) correspond to ~0.24% of the total As, on average. Total, available, and soluble As fractions were strongly and positively correlated with soil Al3+. The PCA indicated that soil pH in combination with CEC might be the key factors controlling soil As concentrations and the occurrence of each arsenic fraction in the soil layers.
Keywords: Amazon; Arsenic; Baseline; Carcinogenic; Extractable As; Prevention level